Problem-based learning in teaching excretory system materials: Does it affect student learning outcomes? - Sogen, Theresia Windywati Bongi; Damopolii, Insar; Kilmaskossu, Johanis Paulus (Inornatus: Biology Education Journal, 2018)
Problem-based learning (PBL) has been reported to be effective in improving student learning outcomes. Excretory system material is difficult material, and students experience problems in learning achievement. This research attempts to use PBM to enhance student learning outcomes about excretory system material. Quasi-experiment was used with a sample of 31 students (15 in the experimental class and 16 in the control class). Data on student learning outcomes were collected using tests. Non-parametric data analysis has been used to calculate learning outcomes data. The results of the research showed that there was no difference in learning outcomes between PBM and conventional classes (p > 0.05). This research concludes that student learning outcomes on excretory system material cannot be optimized by using PBM. It is necessary to optimize PBM implementation in biology classes, such as guidance to students and the use of problems in learning.